WATERFRONT CULTURE SEBAGAI ATRAKSI WISATA TEPIAN AIR - della, prima (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2019)
Abstract: This research is motivated by the lack of reference regarding waterfront culture for students and practitioners that have an impact on education. Aims of this paper is to explore the reference source for waterfront culture as a waterfront tourist attraction. Researchers use various libraries and some empirical facts related to waterfront culture as data. Analysis of content from various literatures then formulated the element which is the fundamental basis of tourist interest in waterfront tourism is the existence of a waterfront culture in the region.Keywords: Waterfront, Culture, AttractionÂ Abstrak: Penelitin ini dilatarbelakangi minimnya refrensi mengenai waterfront culture bagi mahasiswa dan praktisi yang berdampak kepada pendidikan. Untuk itu tulisan ini bertujuan menggali kembali sumber refrensi mengenai waterfront culture sebagai atraksi wisata tepian air. Penelitin menggunkan berbagai pustaka dan beberapa fakta empiri terkait waterfront culture yang ada sebagai data. Analisis konten dari bebagai literatur maka dirumuskan elemen yang menjadi landasan fundamental ketertarikan wisatawan terhadap wisata tepian air adalah keberadaan budaya tepi air (waterfront culture) pada kawasan tersebut.Kata Kunci: Tepian air, Budaya, Atraksi